Pengaruh Win – Win Transportation Solution dan Innovation Terhadap Service Quality pada Bus Transjakarta di Halte Harmoni Jakarta - Anggi Chintya; Tuswoyo Tuswoyo (Jurnal Ilmu Administrasi Publik, 2021)
The background of this thesis is that there are still several problems that occur on the Transjakarta Bus and at Jakarta Harmoni Bus Stop. As with the burning incident of the Transjakarta Bus, a theft case at the Harmoni Bus Stop. Whereas the Transjakarta Bus is a mode of public transportation that should be able to provide security and comfort to Transjakarta Bus users. To overcome some of these problems, an alternative method is needed, namely the Win – Win Transportation Solution and Innovation. This method is helpful so that no one feels disadvantaged, both from the manager and the passengers, and can also attract the community attention more people are expected to use Transjakarta Buses in carrying out their activities. Problem formulation : (1) How big is the effect of Win – Win Transportation Solution to the improvement of Service Quality of Transjakarta Buses at Jakarta Harmoni Bus stop. (2) How big is the effect of Innovation to the improvement of Service Quality of Transjakarta Buses at Jakarta Harmoni Bus Stop. (3) How big is the effect of Win – Win Transportation Solution and Innovation together (simultaneously) on improving Service Quality on Transjakarta Buses at Jakarta Harmoni Bus Stop. Research methods : quantitative approach with associative problem formulation and survey methods. The population in this study is 170.000 Transjakarta Bus users. The sampling technique in this study is accidental sampling and uses the Slovin formula with a Margin of Error 10% / 0,10 and a sig value of 5% / 0,05. From here, the number of samples in this study is obtained for 100 people. Research results : (1) There was a partial influence between Win – Win Transportation Solution to Service Quality because the value was count  > (5,987 > 1,984). (2) There was a partial influence between Innovation to Service Quality because the value was  >  (4,285 > 1,984). (3) There was a simultaneous influence between Win – Win Transportation Solution and Innovation to Service Quality because the value was  (60,914) > than  (3,09).